Where is the cocktail party? Decoding locations of attended and unattended moving sound sources using EEG - Bednar, Adam; Lalor, Edmund C. (NeuroImage (Orlando, Fla.), 2020)
Recently, we showed that in a simple acoustic scene with one sound source, auditory cortex tracks the time-varying location of a continuously moving sound. Specifically, we found that both the delta phase and alpha power of the electroencephalogram (EEG) can be used to reconstruct the sound source azimuth. However, in natural settings, we are often presented with a mixture of multiple competing sounds and so we must focus our attention on the relevant source in order to segregate it from the competing sources e.g. ‘cocktail party effect’. While many studies have examined this phenomenon in the context of sound envelope tracking by the cortex, it is unclear how we process and utilize spatial information in complex acoustic scenes with multiple sound sources. To test this, we created an experiment where subjects listened to two concurrent sound stimuli that were moving within the horizontal plane over headphones while we recorded their EEG. Participants were tasked with paying attention to one of the two presented stimuli. The data were analyzed by deriving linear mappings, temporal response functions (TRF), between EEG data and attended as well unattended sound source trajectories. Next, we used these TRFs to reconstruct both trajectories from previously unseen EEG data. In a first experiment we used noise stimuli and included the task involved spatially localizing embedded targets. Then, in a second experiment, we employed speech stimuli and a non-spatial speech comprehension task. Results showed the trajectory of an attended sound source can be reliably reconstructed from both delta phase and alpha power of EEG even in the presence of distracting stimuli. Moreover, the reconstruction was robust to task and stimulus type. The cortical representation of the unattended source position was below detection level for the noise stimuli, but we observed weak tracking of the unattended source location for the speech stimuli by the delta phase of EEG. In addition, we demonstrated that the trajectory reconstruction method can in principle be used to decode selective attention on a single-trial basis, however, its performance was inferior to envelope-based decoders. These results suggest a possible dissociation of delta phase and alpha power of EEG in the context of sound trajectory tracking. Moreover, the demonstrated ability to localize and determine the attended speaker in complex acoustic environments is particularly relevant for cognitively controlled hearing devices. [Display omitted] •Position of attended moving sound can be decoded from EEG in cocktail party scenario.•Attended sound location was robustly tracked by delta phase and alpha power of EEG.•Unattended speech stimulus trajectory was weakly tracked by delta EEG.•Sound trajectory reconstruction method can be used to decode selective attention.